Automatically Design Convolutional Neural Networks by Optimization With Submodularity and Supermodularity - Hu, Wenzheng; Jin, Junqi; Liu, Tie-Yan; Zhang, Changshui (IEEE transaction on neural networks and learning systems, 2020)
The architecture of convolutional neural networks (CNNs) is a key factor of influencing their performance. Although deep CNNs perform well in many difficult problems, how to intelligently design the architecture is still a challenging problem. Focusing on two practical architectural design problems: to maximize the accuracy with a given forward running time and to minimize the forward running time with a given accuracy requirement, we innovatively utilize prior knowledge to convert architecture optimization problems into submodular optimization problems. We propose efficient Greedy algorithms to solve them and give theoretical bounds of our algorithms. Specifically, we employ the techniques on some public data sets and compare our algorithms with some other hyperparameter optimization methods. Experiments show our algorithms' efficiency.